Content of Data Journalism in Security Topics - Security Media Cell Model Research extracted from a master’s thesis - Karim, Murtadha Muhammed Abdlhussein; Yousef, Layth Badr (ALBAHITH ALALAMI, 2022)
This paper aims at the analytical level to know the security topics that were used with data journalism, and the expression methods used in the statements of the Security Media Cell, as well as to identify the means of clarification used in data journalism. About the Security Media Cell, and the methods preferred by the public in presenting press releases, especially determining the strength of the respondents’ attitude towards the data issued by the Security Media Cell. On the Security Media Cell, while the field study included the distribution of a questionnaire to the public of Baghdad Governorate. The study reached several results, the most important of which is the interest of the security media cell in presenting its data in different ways, the most important of which are narrative texts supported by pictures that express the nature of the security event, and the respondents’ preference for social networking sites in following up on press releases.